Spontaneous Emergent Audiovisual Autoethnography on Tiktok - Urrea Giraldo, Jorge Eduardo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This study analyzes and proposes the concept of "spontaneous audiovisual autoethnography" on TikTok, revealing a diversity of cultural narratives. Autoethnographers like @jairdesdeelcampo0 and @indigenac4mp0 defy conventions, authentically connecting with a global audience. The research is based on content analysis, web observation, and film analysis theory. It highlights the communicative evolution from simple self-narratives to complex and aesthetic representations. The study theoretically defines spontaneous autoethnography on TikTok. This typology transcends borders, projecting rural, ethnic, and peasant life. The present study contributes to understanding new forms of sociocultural expression on digital platforms, emphasizing TikTok's significant impact on preserving audiovisual memory and disseminating diverse voices globally. The research underscores the relevance of the phenomenon in contemporary cultural dynamics and how it amplifies diverse voices globally.